Data collection about failures in fixed partial dentures: 1-year monitoring - Zavanelli, Adriana Cristina; Mazaro, José Vitor Quinelli; NÓbrega, Pâmella Izza; FalcÓn-antenucc, Rosse Mary; Zavanelli, Ricardo Alexandre (Faculdade São Leopoldo Mandic, 2018)
ABSTRACTObjective: The aim of this study was to evaluate the satisfaction of patients rehabilitated with fixed partial denture and the incidence of failures/clinical complications of prostheses after one year.Methods: The patients answered a questionnaire about the satisfaction degree with dental treatment performed and care maintenance for prosthesis conservation. Clinical and radiographic evaluations of the prosthesis were performed. Data were tabulated for descriptive analysis of the factors assessed, with calculation of absolute frequencies and percentages, and chi-square and Fisher’s exact test..Results: A total of 9.67% failures were found. The most common was the prosthesis loosening (57.14%), followed by ceramic fracture (28.57%), and abutment tooth fracture (14.29%). Biological failures were observed in 30.65%. The most common failure was gingival recession (52.00%), periodontal pocket (24.00%), support periodontal involvement (16.00%), and recurrent caries (4.00%). Radiographic examination showed that 70.97% of the total number evaluated had some kind of failure. There was statistically significant association between satisfaction degree and technical failure (p=0.04).Conclusion: Patients were satisfied after observation period of 1 year. The main failures detected were: crown cementation failure and ceramic fracture; gingival recession, periodontal pocket; manufacture and cementation of short intraradicular post with increased diameter and crown cervical misfit.

RESUMOObjetivo: O objetivo deste estudo foi avaliar a satisfação dos pacientes reabilitados com prótese parcial fixa e a incidência de falhas/complicações clínicas das próteses instaladas após um ano.Métodos: Os pacientes responderam um questionário abrangendo o grau de satisfação pelo tratamento odontológico efetuado e os cuidados de manutenção realizados para a conservação da prótese. Na sequência foi realizada avaliação clínica e radiográfica das próteses. Os dados obtidos foram tabulados para análise descritiva dos fatores avaliados com cálculo de frequência absoluta e percentual, e teste de Qui-quadrado e Fischer.Resultados: Foram encontradas 9,67% de falhas, sendo a mais comum a descimentação (soltura da prótese) (57,14%), seguida da fratura da cerâmica (28,57%), e um caso de fratura no dente pilar (14,29%). As falhas biológicas foram observadas em 30,65%. A falha mais comum foi a recessão gengival (52,00%), seguida por bolsa periodontal (24,00%), envolvimento periodonto de suporte (16,00%), e recidiva de cárie (4,00%). No exame radiográfico 70,97% do número total avaliado apresentaram algum tipo de falha. Houve associação estatisticamente significante entre grau de satisfação e falhas mecânicas (p=0,04).Conclusão: Os pacientes ficaram satisfeitos após um período de acompanhamento de 1 ano. As principais falhas detectadas foram: falha de cimentação da coroa e fratura da cerâmica; Recessão gengival, bolsa periodontal; confecção e cimentação de pino intraradicular curto, pino com diâmetro aumentado e desajuste cervical da coroa.
Levantamento das falhas em prótese parcial fixa: acompanhamento de um ano
Keywords: Patient satisfaction; Fixed partial denture; Failures; Satisfação do paciente; Prótese parcial fixa; falhas